Effect of intensive endurance training on rat brain and hepatic 8-oxoguanine DNA glycosylase and 8-hydroxy-2'-deoxyguanosine levels - Mohammad Esmaiel Afzalpour, Hossein TaheriChadorneshin, Seyed-Hosein Abtahi-Eivary, Ehsan Afroozi-Gerow (Journal of Applied Pharmaceutical Science, 2016)
The purpose of this study was to investigate the effect of intensive endurance training on 8-oxoguanine DNA glycosylase (OGG1) and 8-hydroxy-2'-deoxyguanosine (8-OHdG) levels in liver and brain of rats. 16 adult and male albino wistar rats were randomly divided into sedentary control and endurance exercise training groups. Animals ran on treadmill for 6 weeks, 6 days a week, at a speed of 10 m/min (85 percent of maximal oxygen consumption). The content of OGG1 and 8-OHdG were measured using sandwich ELISA assay. Data analyzed using Student’s T-test at P≤0.05 level. Our results showed that intensive endurance training has no significant effect on 8-OHdG contents in liver (t14=1.09, p=0.29) and brain (t14=0.93, p=0.36) of rats. However, contents of OGG1 in liver (t14=5.84, p=0.001) and brain (t14=4.09, p=0.001) of rats significant increases following intensive endurance training. Finally, there were no significantly differences between changes in contents of 8-OHdG (t14=0.44, p=0.66) and OGG1 (t14=1.72, p=0.10) in liver and brain of rats following endurance training. Intensive endurance training maintains 8-OHdG genomic damage in baseline level in liver and brain of rats by increasing contents of OGG1.
Keywords: Endurance training, hydroxy deoxyguanosine, Liver, Brain